No effect of C-reactive protein on early atherosclerosis in LDLR-/- / human C-reactive protein transgenic mice - Torzewski, Michael; Reifenberg, Kurt; Cheng, Fei; Wiese, Elena; Küpper, Ines; Crain, Jeanine; Lackner, Karl J; Bhakdi, Sucharit (Thrombosis and Haemostasis, 2008)
The association between increased concentrations of C-reactive protein (CRP) and future cardiovascular events is well established. However, it is currently unclear whether this clinical observation represents an epiphenomenon or whether the pentraxin may actively promote the development of atherosclerosis. Experimental studies with knockout mice with a defect in apolipoprotein E (ApoE-/-) have been used to investigate the role of CRP in atherogenesis, but the results obtained have been contradictory so far. Since knockout mice with a defect in low density lipoprotein receptor (LDLR-/-) may represent a better model of atherogenesis compared to ApoE-/- animals, we undertook experiments to investigate the atherogenic potential of CRP using LDLR-/- knockout mice. We crossbred CRP transgenic animals expressing the human CRP pentraxin (huCRP) to LDLR-/- mice, fed the resulting double mutants a pro-atherogenic Western type diet (WTD) for four, eight or 12 weeks, respectively, and quantitated atherosclerotic lesion development. Significant differences of lesion size or lesion composition could not be detected between the huCRP-positive LDLR-/- mice and the huCRP–negative LDLR-/- controls corroborating the contention that CRP does not play a pathogenetic role in early murine atherogenesis.
Keywords: LDLR mice; CRP; atherosclerosis